Database and expert systems applications : DEXA 2018 International Workshops, BDMICS, BIOKDD, and TIR, Regensburg, Germany, September 3-6, 2018, Proceedings /: DEXA 2018 International Workshops, BDMICS, BIOKDD, and TIR, Regensburg, Germany, September 3-6, 2018, Proceedings. (2018) - Unknown
No abstract available